In situ metalation of free base phthalocyanine covalently bonded to silicon surfaces - Lupo, Fabio; Tudisco, Cristina; Bertani, Federico; Dalcanale, Enrico; Condorelli, Guglielmo G. (Beilstein Journal of Nanotechnology, 2014)
Free 4-undecenoxyphthalocyanine molecules were covalently bonded to Si(100) and porous silicon through thermic hydrosilylation of the terminal double bonds of the undecenyl chains. The success of the anchoring strategy on both surfaces was demonstrated by the combination of X-ray photoelectron spectroscopy with control experiments performed adopting the commercially available 2,3,9,10,16,17,23,24-octakis(octyloxy)-29H,31H-phthalocyanine, which is not suited for silicon anchoring. Moreover, the study of the shape of the XPS N 1s band gave relevant information on the interactions occurring between the anchored molecules and the substrates. The spectra suggest that the phthalocyanine ring interacts significantly with the flat Si surface, whilst ring–surface interactions are less relevant on porous Si. The surface-bonded molecules were then metalated in situ with Co by using wet chemistry. The efficiency of the metalation process was evaluated by XPS measurements and, in particular, on porous silicon, the complexation of cobalt was confirmed by the disappearance in the FTIR spectra of the band at 3290 cm−1 due to –NH stretches. Finally, XPS results revealed that the different surface–phthalocyanine interactions observed for flat and porous substrates affect the efficiency of the in situ metalation process.
Keywords: metalation; phthalocyanine; silicon surface; surface functionalization; X-ray photoelectron spectroscopy (XPS)

(untitled) - Baran, J. D.; Larsson, J. A. (J. Phys. Chem. C, 2013)

(untitled) - Walter, M. G.; Rudine, A. B.; Wamser, C. C. (J. Porphyrins Phthalocyanines, 2010)

(untitled) - Claessens, C. G.; Hahn, U.; Torres, T. (Chem. Rec., 2008)

(untitled) - Bohrer, F. I.; Colesniuc, C. N.; Park, J.; Ruidiaz, M. E.; Schuller, I. K.; Kummel, A. C.; Trogler, W. C. (J. Am. Chem. Soc., 2009)

(untitled) - Sorokin, A. B. (Chem. Rev., 2013)

(untitled) - Dolmans, D. E. J. G. J.; Fukumura, D.; Jain, R. K. (Nat. Rev. Cancer, 2003)

(untitled) - Cárdenas-Jirón, G. I.; Leon-Plata, P.; Cortes-Arriagada, D.; Seminario, J. M. (J. Phys. Chem. C, 2011)

(untitled) - Klar, D.; Klyatskaya, S.; Candini, A.; Krumme, B.; Kummer, K.; Ohresser, P.; Corradini, V.; de Renzi, V.; Biagi, R.; Joly, L.; Kappler, J. P.; del Pennino, U.; et al. (Beilstein J. Nanotechnol., 2013)

(untitled) - Chen, S.; Liu, Y.; Xu, Y.; Sun, Y.; Qiu, W.; Sun, X.; Zhu, D. (Synth. Met., 2006)

(untitled) - Li, Z.; Lieberman, M.; Hill, W. (Langmuir, 2001)

(untitled) - Alfredsson, Y.; Åhlund, J.; Nilson, K.; Kjeldgaard, L.; O’Shea, J. N.; Theobald, J.; Bao, Z.; Mårtensson, N.; Sandell, A.; Puglia, C.; Siegbahn, H. (Thin Solid Films, 2005)

(untitled) - Huc, V.; Armand, F.; Bourgoin, J. P.; Palacin, S. (Langmuir, 2001)

(untitled) - Trelka, M.; Urban, C.; Rogero, C.; de Mendoza, P.; Mateo-Marti, E.; Wang, Y.; Silanes, I.; Écija, D.; Alcamì, M.; Yndurain, F.; Arnau, A.; Martın, F.; et al. (CrystEngComm, 2011)

(untitled) - Buriak, J. M. (Chem. Rev., 2002)

(untitled) - Biavardi, E.; Tudisco, C.; Maffei, F.; Motta, A.; Massera, C.; Condorelli, G. G.; Dalcanale, E. (Proc. Natl. Acad. Sci. U. S. A., 2012)

(untitled) - Biavardi, E.; Federici, S.; Tudisco, C.; Menozzi, D.; Massera, C.; Sottini, A.; Condorelli, G. G.; Bergese, P.; Dalcanale, E. (Angew. Chem., Int. Ed., 2014)

(untitled) - Kumar, G. A.; Thomas, J.; Unnikrishnan, N. V.; Nampoori, V. P. N.; Vallabhan, C. P. G. (J. Porphyrins Phthalocyanines, 2001)

(untitled) - Massimi, L.; Lisi, S.; Pacilè, D.; Mariani, C.; Betti, M. G. (Beilstein J. Nanotechnol., 2014)

(untitled) - Sperl, A.; Kröger, J.; Berndt, R. (Angew. Chem., Int. Ed., 2011)

(untitled) - Bai, Y.; Buchner, F.; Wendahl, M. T.; Kellner, I.; Bayer, A.; Steinrück, H.-P.; Marbach, H.; Gottfried, J. M. (J. Phys. Chem. C, 2008)

(untitled) - Leclaire, J.; Dagiral, R.; Pla-Quintana, A.; Caminade, A.-M.; Majoral, J.-P. (Eur. J. Inorg. Chem., 2007)

(untitled) - Görlach, B.; Hellriegel, C.; Steinbrecher, S.; Yüksel, H.; Albert, K.; Plies, E.; Hanack, M. (J. Mater. Chem., 2001)

(untitled) - Boukherroub, R.; Morin, S.; Sharpe, P.; Wayner, D. D. M.; Allongue, P. (Langmuir, 2000)

(untitled) - Swift, P. (Surf. Interface Anal., 1982)

(untitled) - Killampalli, A. S.; Ma, P. F.; Engstrom, J. R. (J. Am. Chem. Soc., 2005)

(untitled) - Dube, A.; Chadeayne, A. R.; Sharma, M.; Wolczanski, P. T.; Engstrom, J. R. (J. Am. Chem. Soc., 2005)

(untitled) - Condorelli, G. G.; Motta, A.; Bedoya, C.; Di Mauro, A.; Pellegrino, G.; Smecca, E. (Inorg. Chim. Acta, 2007)

(untitled) - Palmgren, P.; Nilson, K.; Yu, S.; Hennies, F.; Angot, T.; Nlebedim, C. I.; Layet, J.-M.; Le Lay, G.; Göthelid, M. (J. Phys. Chem. C, 2008)

(untitled) - Yu, S.; Ahmadi, S.; Sun, C.; Adibi, P. T. Z.; Chow, W.; Pietzsch, A.; Göthelid, M. (J. Chem. Phys., 2012)

(untitled) - Mattioli, G.; Filippone, F.; Giannozzi, P.; Caminiti, R.; Bonapasta, A. A. (Chem. Mater., 2009)

(untitled) - Mannini, M.; Bertani, F.; Tudisco, C.; Malavolti, L.; Poggini, L.; Misztal, K.; Menozzi, D.; Motta, A.; Otero, E.; Ohresser, P.; Sainctavit, P.; Condorelli, G. G.; et al. (Nat. Commun., 2014)

(untitled) - Tudisco, C.; Trusso Sfrazzetto, G.; Pappalardo, A.; Motta, A.; Tomaselli, G. A.; Fragalà, I. L.; Ballistreri, F. P.; Condorelli, G. G. (Eur. J. Inorg. Chem., 2011)

(untitled) - Petraki, F.; Peisert, H.; Uihlein, J.; Aygül, U.; Chassé, T. (Beilstein J. Nanotechnol., 2014)

(untitled) - Petraki, F.; Peisert, H.; Biswas, I.; Chassé, T. (J. Phys. Chem. C, 2010)

(untitled) - Guo, J.; Li, H.; He, H.; Chu, D.; Chen, R. (J. Phys. Chem. C, 2011)

(untitled) - Shubina, T. E.; Marbach, H.; Flechtner, K.; Kretschmann, A.; Jux, N.; Buchner, F.; Steinrück, H.-P.; Clark, T.; Gottfried, J. M. (J. Am. Chem. Soc., 2007)

(untitled) - Condorelli, G. G.; Motta, A.; Favazza, M.; Fragala, I. L.; Busi, M.; Menozzi, E.; Dalcanale, E.; Cristofolini, L. (Langmuir, 2006)

(untitled) - Gulino, A.; Lupo, F.; Condorelli, G. G.; Fragalà, M. E.; Amato, M. E.; Scarlata, G. (J. Mater. Chem., 2008)

(untitled) - Tudisco, C.; Betti, P.; Motta, A.; Pinalli, R.; Bombaci, L.; Dalcanale, E.; Condorelli, G. G. (Langmuir, 2012)

(untitled) - Briggs, D.; Beamson, G. (Anal. Chem., 1992)